Bureaucracy as a form of organizational management considering the millennial discourse: theoretical reflection - Zurita Mézquita, Efraín Canaán (2022)
Bureaucratic thinking exists within administrative theories, with a long tradition in organizational management; however, the hegemonic perspectives of bureaucratic management are currently being debated in the face of the millennial discourse. The main objective of this work was to examine the characteristics of the millennial generation and its influence on the bureaucratic management style of current companies in the Western world, considering two theoretical aspects: the bureaucratic school of thought applied to the management of organizations and the way in which millennials have influenced the form of management with their arrival in the business field. Methodologically, this work was exploratory in nature and through a documentary review, searching in databases of articles in indexed journals, books and university theses. As a conclusion, it was found that the theory of bureaucratic organizations in the western capitalist world facilitates specialization, centralization and formalization of employees, processes and functions; although they also generate delays and situations of discontent for workers. Companies need to encourage employee creativity, facilitate processes and streamline adaptability to a digital environment. This study leaves open lines of research on counterproductive work behaviors in millennial employees; likewise, it is necessary to evaluate whether the size, line of business or industry influences the discourse on this generation and the characterization that has been given in empirical studies on them.